Comparative Analysis of Building Information Modeling (BIM) Patterns and Trends in the United Arab Emirates (UAE) with Developed Countries - Salem Buhashima Abdalla; Mamun Rashid; Moohammed Wasim Yahia; Emad Mushtaha; Alex Opoku; Ahmad Sukkar; Aref Maksoud; Rawan Hamad (Buildings, 2023)
This research seeks to gain a deeper understanding of the current ecosystem of BIM technology and its utilization in the UAE. Since the UAE has been an early adopter of BIM, its utilization of BIM is now likely to reach that of developed nations. By adopting the BIM case study analysis framework, two sets of projects of similar categories in terms of functionality and typology were selected and mapped. One set represents projects within the UAE, and the second represents projects from developed nations utilizing BIM during the projects’ lifecycle (LC). Incorporating expert interviews to triangulate the results collected from the case study analysis will further contribute to developing a more in-depth comprehension of BIM use in the UAE. The three significant inferences can be drawn from the findings. Firstly, in the UAE, stakeholders utilize BIM fragmentarily in different stages. Secondly, the full extent of BIM utilization over the project’s LC is not pursued. Thirdly, no effective BIM standards or protocols exist. Even though international firms are the main drivers of UAE BIM adoption and utilization, UAE BIM is still in its infancy, necessitating a more collaborative effort to realize the holistic benefits of the BIM process. The findings could be utilized to identify industry standards and guiding principles for BIM implementation in the UAE and help identify areas for improvement. It also provides valuable insights into how BIM can be used more effectively in the country and how its use can be promoted. Additionally, it could be used as a guide for owners/asset managers and AEC professionals in the UAE looking to implement BIM in their projects.